Pengaruh Pengembangan Karir terhadap Kinerja Karyawan pada Kantor Industri Kapal Indonesia (Persero) Kota Makassar - Rilfan Kasi’ Ranteta’dung; Kristison Tobeoto; Ayu Latifah Alfisyahrin; Andi Mattingaragau Tenrigau (CV. Ulil Albab Corp, 2023)
The aim of this research is to find out whether career development influences the performance of PT employees. Indonesian Ship Industry (Persero) Makassar City. The method used in writing is quantitative analysis with the help of the SPSS version 25 program. Meanwhile, the analysis technique used is simple linear regression to prove whether career development significantly influences employee performance. The results of this research are that there is a positive and significant influence, which is indicated by the presence of a sig value. of 0.000, and the coefficient of determination (R2) of 0.466, which means that career development factors contribute to employee performance by 46.6% and the rest is influenced by other factors. The results of this research have implications for improving employee performance, especially at PT. Indonesian Ship Industry (Persero) Makassar City